Cone beam computed tomography after round window vibroplasty: do the radiological findings match the auditory outcome?. (April 2015) - Barbara, Maurizio; Volpini, Luigi; Ciotti, Mario; Filippi, Chiara; Covelli, Edoardo; Monini, Simonetta; D'Ambrosio, Ferdinando
Abstract: Conclusion: The cone beam computed tomography (CBCT) imaging technique has proved to be reliable for assessing the appropriate positioning of the floating mass transducer (FMT) in the round window (RW) niche, although some parameters do not seem to be essential for achieving a satisfactory functional outcome. Objectives: To evaluate the role that specific imaging parameters derived from CBCT of the temporal bone have for predicting the functional outcome after RW vibroplasty (RW-VP). Methods: CBCT imaging was carried out in a homogeneous group of patients who presented with a mixed type of hearing loss after open tympanoplasty. Three arbitrary radiological parameters were taken into account: the FMT/RW membrane contact, bony contacts of the FMT margins, and the inferior FMT tissue support. The audiological assessment took into consideration the PTA4 (500–4000 Hz), the PTA2 (125–250 Hz), and the word recognition score (WRS) in quiet and in noise. Results: One subject presented with all positive CBCT parameters and showed a good, but not the best auditory performance among the study group. In the majority of the subjects, with a satisfactory postoperative hearing improvement, at least two of the three radiological parameters were present. In comparison with the unaided condition, an improvement in both the PTA4 and PTA2 was found in all the subjects.